Analysis and comparison of ant colony optimization algorithm with DSDV, AODV, and AOMDV based on shortest path in MANET. Issue 2 (17th February 2020) - Sinwar, Deepak; Sharma, Nisha; Maakar, Sunil Kumar; Kumar, Sudesh
Abstract: Due to the dynamic nature of Mobile Ad hoc NETwork (MANET) the designing and development of protocols is very challenging. MANET has a limited number of resources i.e., power, infrastructure, etc. The need for an optimized path for communication amongst node has attracted the use of Swarm Intelligence (SI) based techniques such as Ant-Colony Optimization (ACO), Particle Swarm Optimization (PSO). In sort to broaden the duration of communication availability, the protocol needs to be optimized for finding out the greatest path. SI based techniques are able to solve these numerous routing problems. ACO provides the optimized packet delivery rate, throughput with low power consumption and packet delay. This paper compares the performance of various existing routing protocols viz. AODV, AOMDV as reactive, DSDV as proactive and ACOP using Random Waypoint Mobility Model. The purpose of using this mobility model is generating different scenarios for the same purpose. The analysis of these protocols has been made by implementing irregularities in the scenario using Network Simulator (NS2). Various performance metrics including Packet Delivery Fraction, Throughput and End to end Delay are used for validating the comparative study. Experimental results of the simulation indicate that the performance of the ACOP protocol is found better than other protocols of study.